Penggunaan aplikasi quizizz sebagai media pembelajaran dan asesmen pada materi bahasa Inggris - Khori Putri Ramadhani; Havid Ardi (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2021)
The presence of digital media give solution for teacher to produce and use multimedia such as Quizizz. This article aims to explain how to use Quizizz application for teachers. It used a library research design, because the research reading and understanding some articles that relate to this study. Based on the analysis, it can be explained that there are three steps of using Quizizz application. The first step is how to sign up and log in to Quizizz. The second step is how to use quizzes from the application. The third step is how to create a quiz by self. The fourth step is how to create a presentation in Quizizz. Therefore, it is very useful for teachers to conduct the Quizizz application in the classroom.